2022
DOI: 10.1039/d2en00499b
|View full text |Cite
|
Sign up to set email alerts
|

Raspberry-like TiO2 hollow spheres consisting of small nanocrystals towards efficient NO removal

Abstract: The conversion of nitrogen oxide (NO) by photocatalysis is promising to solve the increasingly serious air pollution. Herein, raspberry-like TiO2 hollow spheres consisted of small nanocrystals (less than 10 nm)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 74 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…This result fully conrms the high mineralization ability of CdS/ZnIn 2 S 4 /g-C 3 N 4 -0.2 for RhB. The stability is a crucial factor affecting the actual application of the photocatalyst, 56 and thus sequential cycling experiments were performed to detect the stability of the CdS/ ZnIn 2 S 4 /g-C 3 N 4 -0.2 ternary photocatalyst. As displayed in Fig.…”
Section: Resultsmentioning
confidence: 76%
“…This result fully conrms the high mineralization ability of CdS/ZnIn 2 S 4 /g-C 3 N 4 -0.2 for RhB. The stability is a crucial factor affecting the actual application of the photocatalyst, 56 and thus sequential cycling experiments were performed to detect the stability of the CdS/ ZnIn 2 S 4 /g-C 3 N 4 -0.2 ternary photocatalyst. As displayed in Fig.…”
Section: Resultsmentioning
confidence: 76%
“…[84][85][86][87][88][89] Among these, heterostructure construction based on the idea of nanoarchitectonics provides a clear picture on extending the possibilities of g-C 3 N 4 materials in photo/electro- catalysis. [90][91][92][93][94][95][96][97][98][99] Although numerous paper has been reported on construction of different types of g-C 3 N 4 based heterostructures, exploitation on the ultrathin g-C 3 N 4 material nanoarchitectonics is still at an early stage. [65,[95][96][97][98][99] Nanoarchitectonics of ultrathin g-C 3 N 4 heterostructure material (involving Type II, S-scheme and Z-scheme) that aims for enhancing photocatalytic H 2 generation and CO 2 reduction performances will be discussed in the following section.…”
Section: General Properties and Synthesis Of G-c 3 N 4 Nanosheetsmentioning
confidence: 99%
“…Doping, defects engineering, interfacial engineering, and nanostructure construction are popular methodologies for improving the photocatalytic performance of novel g‐C 3 N 4 catalysts [84–89] . Among these, heterostructure construction based on the idea of nanoarchitectonics provides a clear picture on extending the possibilities of g‐C 3 N 4 materials in photo/electro‐catalysis [90–99] . Although numerous paper has been reported on construction of different types of g‐C 3 N 4 based heterostructures, exploitation on the ultrathin g‐C 3 N 4 material nanoarchitectonics is still at an early stage [65,95–99] .…”
Section: General Properties and Synthesis Of G‐c3n4 Nanosheetsmentioning
confidence: 99%
“…Therefore, at present, research work in this area is focused on developing catalysts with high efficiency and stability in an aqueous medium. For this purpose, a lot of researchers have validated that encapsulation of metal complexes inside a carbon-based substrate, such as graphene, carbon nitrides, etc., increases the stability and efficiency of water splitting and supercapacitor applications and other applications. , Among the reported carbon substrate materials, two-dimensional carbon nitride (g-C 3 N 4 ), having higher nitrogen content, is gaining importance as a catalyst for supercapacitor and water-splitting applications in recent times. , However, it possesses fewer active sites and high resistance that limit their applications. To overcome this issue, g-C 3 N 4 combined with metal complexes or metal oxides has been explored and it has been found that the introduction of these catalysts increases its active site, thereby increasing its efficiency. , Several g-C 3 N 4 composites with metal oxides, metals, carbon, and metal phosphides have been studied for water-splitting activity, and it has been found that the catalyst’s incorporation into the g-C 3 N 4 matrix improves the performance.…”
Section: Introductionmentioning
confidence: 99%